In Vitro Intraductal MRI and T2 Mapping of Cholangiocarcinoma Using Catheter Coils - Khuntikeo N (Hepatic Medicine : Evidence and Research, 2020)
Narong Khuntikeo,1 Attapol Titapun,1 Nittaya Chamadol,2 Wuttisak Boonphongsathien,2 Prakasit Sa-Ngiamwibool,3 Simon D Taylor-Robinson,4 Christopher A Wadsworth,4 Shuo Zhang,5 Evdokia M Kardoulaki,6 Richard RA Syms6 1Department. of Surgery, Faculty of Medicine, Khon Kaen University, Khon Kaen, 40002, Thailand; 2Department of Radiology, Faculty of Medicine, Khon Kaen University, Khon Kaen 40002, Thailand; 3Department of Pathology, Faculty of Medicine, Khon Kaen University, Khon Kaen 40002, Thailand; 4Division of Surgery and Cancer, Imperial College London, Paddington, London W2 1NY, UK; 5Philips Healthcare Germany, Health Systems, Clinical Science, Hamburg, Germany; 6EEE Department, Imperial College, London SW7 2AZ, UKCorrespondence: Simon D Taylor-RobinsonDivision of Surgery and Cancer, Imperial College London, Liver Unit, St. Mary’s Hospital, South Wharf Road, Paddington, London W2 1NY, UKTel +44 20 3312 6199Email s.taylor-robinson@imperial.ac.ukAim: Diagnostic imaging of early-stage cholangiocarcinoma is challenging. A previous in vitro study of fixed-tissue liver resection specimens investigated T2 mapping as a method of exploiting the locally increased signal-to-noise ratio (SNR) of duodenoscope coils for improved quantitative magnetic resonance imaging (MRI), despite their non-uniform sensitivity. This work applies similar methods to unfixed liver specimens using catheter-based receivers.Methods: Ex vivo intraductal MRI and T2 mapping were carried out at 3T on unfixed resection specimens obtained from cholangiocarcinoma patients immediately after surgery using a catheter coil based on a thin-film magneto-inductive waveguide, inserted directly into an intrahepatic duct.Results: Polypoid intraductal cholangiocarcinoma was imaged using fast spin-echo sequences. High-resolution T2 maps were extracted by fitting of data obtained at different echo times to mono-exponential models, and disease-induced changes were correlated with histopathology. An increase in T2 was found compared with fixed specimens and differences in T2 allowed the resolution of tumour tissue and malignant features such as polypoid morphology.Conclusion: Despite their limited field of view, useful data can be obtained using catheter coils, and T2 mapping offers an effective method of exploiting their local SNR advantage without the need for image correction.Keywords: Cholangiocarcinoma, T2 mapping, catheter coil